Oral cleanliness in daily users of powered vs. manual toothbrushes – a cross-sectional study - Waldemar Petker; Ulrike Weik; Jutta Margraf-Stiksrud; Renate Deinzer (BMC Oral Health, 2019)
Abstract Background Toothbrushing is a daily routine. Still, when adults are asked to manually perform oral hygiene to the best of their abilities, a considerable amount of plaque persists. Little is known about the performance of people who use a powered toothbrush. The present study thus analysed whether the capability to achieve oral cleanliness is better in people for whom powered toothbrushing is a daily routine. Methods University students, who either performed powered (N = 55) or manual (N = 60) toothbrushing for more than 6 months on a daily basis were asked to clean their teeth to the best of their abilities by their own device. Plaque was assessed prior to and immediately after brushing. Furthermore, gingival bleeding, recessions, periodontal pocket depths and dental status were assessed. Oral hygiene performance was video-taped and analyzed with respect to brushing duration, sites of brushing and application of interproximal cleaning devices. Results No differences between groups were found with respect to plaque before and after brushing, clinical parameters and overall brushing duration (all p > 0.05, all d < 0.156). After brushing, plaque persisted at approximately 40% of the sections adjacent to the gingival margin in both groups. Conclusions No advantage of daily powered toothbrushing as compared to daily manual toothbrushing was seen with respect to oral hygiene or clinical parameters. The capability to achieve oral cleanliness was low, irrespective of the type of toothbrush under consideration. Additional effort is thus needed to improve this capability.